Capsule Enlargement in Cryptococcus neoformans Is Dependent on Mitochondrial Activity - Trevijano-Contador, Nuria; Rossi, Suelen A.; Alves, Elisabete; Landín-Ferreiroa, Santiago; Zaragoza, Oscar (Frontiers in Microbiology, 2017)
Cryptococcus neoformans is an environmental encapsulated yeast that behaves as an opportunistic pathogen in immunocompromised individuals. The capsule is the main virulence factor of this pathogen. This structure is highly dynamic, and it can change its size and structure according to the environmental conditions. During infection, C. neoformans significantly enlarges the size of the capsule by the addition of new polysaccharide. It is believed that capsule growth is an energy-cost process, but this aspect has never been addressed. In this work, we have evaluated the role of mitochondrial activity on capsule growth using specific inhibitors of the electron respiratory chain. We observed that capsule growth was impaired in the presence of inhibitors of the respiratory chain as salicylhydroxamic acid (SHAM) or antimycin A. Furthermore, capsule growth correlated with an increase of the mitochondrial membrane potential and higher production of reactive oxygen species. Our results confirm that capsule growth depends on mitochondrial activity, and open new insights to understand the regulation of this process.